Penerapan Model Project Based Learning Berbantuan Media Komik Digital Untuk Meningkatkan Kreativitas Siswa Kelas IV di SDN Sukomoro Kediri - Priska Auliawati; Cicilia Ika Rahayu Nita; Sriatun Sriatun; Priska Auliawati; Cicilia Ika Rahayu Nita (Universitas Negeri Malang, 2023)
Abstract: This research is motivated by the low creativity of students in thematic subjects. Based on the results of observations made to 27 students, there were 9 students belonging to the good category in terms of creativity. This study purposes to describe the Project Based Learning model application assisted by digital comic media to increase the creativity of fourth grade students at SDN Sukomoro on thematic subjects theme 8. The Classroom Action Research on Kemmis and Mc.Taggart model is applied at twice meetings in two cycles that consists of planning, action, observe, and reflection phase. The observation on students and teacher, interview with teacher, also other review documents are used as data sources to analyze on the approach of quantitative and qualitative descriptive analysis. This study find that the increasing of students’ creativity on pre-cycle with 33,33 percent, increased in cycle I to 68.18 percent and in cycle II increased to 81.48 percent. So it can be concluded that classroom action research with the Project Based Learning model assisted by digital comic media can be said to be successfully applied to increase the creativity of fourth grade students at SDN Sukomoro in theme 8 thematic subjects. Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya kreativitas siswa pada mata pelajaran tematik. Berdasarkan hasil observasi yang dilakukan kepada 27 siswa ,terdapat 9 siswa tergolong dalam kategori baik tingkat kreativitasnya. Tujuan dari penelitian ini adalah untuk mendeskripsikan penerapan model Project Based Learning berbantuan media komik digital untuk meningkatkan kreativitas siswa kelas IV di SDN Sukomoro pada mata pelajaran tematik tema 8. Penelitian Tindakan Kelas (PTK) model Kemmis dan Mc. Taggart diterapkan pada dua kali pertemuan dalam dua siklus yang terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi. Observasi pada siswa dan guru, wawancara dengan guru, serta kajian dokumen lain sebagai sumber data untuk dianalisis pada pendekatan analisis deskriptif kuantitatif dan kualitatif. Penelitian menemukan peningkatan kreativitas siswa pada pra siklus 33,33 persen meningkat pada siklus I menjadi 68,18 persen dan pada siklus II meningkat menjadi 81,48 persen. Sehingga dapat disimpulkan bahwa penelitian tindakan kelas dengan model Project Based Learning berbantuan media komik digital ini dapat dikatakan berhasil diterapkan untuk meningkatkan kreativitas siswa kelas IV di SDN Sukomoro pada mata pelajaran tematik tema 8.